The national burden of influenza‐associated severe acute respiratory illness hospitalization in Zambia, 2011‐2014. Issue 1 (15th December 2017) - Theo, Andros; Tempia, Stefano; Cohen, Adam L; Simusika, Paul; Chentulo, Edward; Chikamukwa, Chikama Mukwangole; Monze, Mwaka
Abstract : Background: Estimates of influenza‐associated hospitalization are limited in low‐ and middle‐income countries, especially in Africa. Objective: To estimate the national number of influenza‐associated severe acute respiratory illness (SARI) hospitalization in Zambia. Methods: We conducted active prospective hospital‐based surveillance for SARI at the University Teaching Hospital (UTH) situated in Lusaka Province during 2011‐2014. Upper respiratory tract samples were tested for influenza virus using a reverse transcriptase polymerase chain reaction assay. We estimated age‐specific rates of influenza‐associated SARI hospitalizations for the UTH using census and secondary data on respiratory hospitalizations following estimation approaches recommended by the World Health Organization. We used the UTH hospitalization rates as a proxy for Lusaka Province. These rates were adjusted for each of the remaining 9 provinces based on their prevalence of risk factors for pneumonia and healthcare‐seeking behavior. Rates were expressed per 100, 000 population. Results: SARI cases accounted for 77.1% (13 389/17 354) of respiratory admissions at the UTH; 82.7% (11 859/14 344) and 50.8% (1530/3010) among individuals aged <5 and ≥5 years, respectively. Among SARI cases tested, the influenza virus detection rate was 5.5% (152/2734), 4.8% (48/998), and 6.0% (104/1736) among individuals aged <5 and ≥5 years, respectively. The mean annual national number of influenza‐associated SARI hospitalizations was 6181 (95% CI: 4321‐8041—rate: 43.9; 95% CI: 30.7‐57.1); 4669 (95% CI: 3287‐6051—rate: 187.7; 95% CI: 132.1‐243.3) among children aged <5 years; and 1512 (95% CI: 1037‐1987—rate: 13.1; 95% CI: 9.0‐17.2) among individuals aged ≥5 years. Conclusions: The burden of influenza‐associated SARI hospitalizations was substantial and was highest among children aged <5 years.